Siglec-8 Signals Through a Non-Canonical Pathway to Cause Human Eosinophil Death In Vitro - Carroll, Daniela J.; Cao, Yun; Bochner, Bruce S.; O’Sullivan, Jeremy A. (Frontiers in Immunology, 2021)
Sialic acid-binding immunoglobulin-like lectin (Siglec)-8 is a glycan-binding receptor bearing immunoreceptor tyrosine-based inhibitory and switch motifs (ITIM and ITSM, respectively) that is selectively expressed on eosinophils, mast cells, and, to a lesser extent, basophils. Previous work has shown that engagement of Siglec-8 on IL-5–primed eosinophils causes cell death via CD11b/CD18 integrin–mediated adhesion and NADPH oxidase activity and identified signaling molecules linking adhesion, reactive oxygen species (ROS) production, and cell death. However, the proximal signaling cascade activated directly by Siglec-8 engagement has remained elusive. Most members of the Siglec family possess similar cytoplasmic signaling motifs and recruit the protein tyrosine phosphatases SHP-1/2, consistent with ITIM-mediated signaling, to dampen cellular activation. However, the dependence of Siglec-8 function in eosinophils on these phosphatases has not been studied. Using Siglec-8 antibody engagement and pharmacological inhibition in conjunction with assays to measure cell-surface upregulation and conformational activation of CD11b integrin, ROS production, and cell death, we sought to identify molecules involved in Siglec-8 signaling and determine the stage of the process in which each molecule plays a role. We demonstrate here that the enzymatic activities of Src family kinases (SFKs), Syk, SHIP1, PAK1, MEK1, ERK1/2, PLC, PKC, acid sphingomyelinase/ceramidase, and Btk are all necessary for Siglec-8–induced eosinophil cell death, with no apparent role for SHP-1/2, SHIP2, or c-Raf. While most of these signaling molecules are necessary for Siglec-8–induced upregulation of CD11b integrin at the eosinophil cell surface, Btk is phosphorylated and activated later in the signaling cascade and is instead necessary for CD11b activation. In contrast, SFKs and ERK1/2 are phosphorylated far earlier in the process, consistent with their role in augmenting cell-surface levels of CD11b. In addition, pretreatment of eosinophils with latrunculin B or jasplakinolide revealed that actin filament disassembly is necessary and sufficient for surface CD11b integrin upregulation and that actin polymerization is necessary for downstream ROS production. These results show that Siglec-8 signals through an unanticipated set of signaling molecules in IL-5–primed eosinophils to induce cell death and challenges the expectation that ITIM-bearing Siglecs signal through inhibitory pathways involving protein tyrosine phosphatases to achieve their downstream functions.